Study of the Mastery of Digital Self-Efficacy through the Learning Process among Students of Universities in the Livestock Sector - Ayu Intan Sari; Ida Nugroho Saputro; Sutrisno Hadi Purnomo; Endang Tri Rahayu; Shanti Emawati (Qubahan Academic Journal)
Mastery of digital skills is essential for animal husbandry students because digital technology has changed the way of work and innovation in the livestock industry. With digital skills, students can optimize livestock management, track livestock health and reproduction, and predict market developments more efficiently. Perceptions of self-efficacy regarding the ability to use digital technology will encourage increased digital skills for students. Many studies examine digital skills, but limited studies discuss how digital self-efficacy is formed by involving institutional support, instructor influence, peer influence, and digital literacy. Therefore, this study examines a structural model for forming digital self-efficacy involving institutional support, instructor influence, peer influence, and digital literacy. A total of 263 students were involved in filling out the research questionnaire. This study uses structural equation modeling (SEM) analysis with SmartPLS software. The study results reveal that digital self-efficacy is directly influenced by peer influence and digital literacy. Meanwhile, institutional support and instructor influence do not directly affect digital self-efficacy. Another finding, digital literacy mediates the influence of institutional support, instructor influence, and peer influence on student digital self-efficacy. This study discusses in depth how to master digital self-efficacy through the learning process on campus and the implications of this study for universities.